Electromagnetics for engineers - Ulaby, Fawwaz T. (Fawwaz Tayssir), 1943- (Upper Saddle River, NJ : Pearson/Prentice Hall, 2005)
Accompanying CD-ROM serves as an interactive self-study supplement to the text and includes exercises and solved problems
Book is accompanied by one computer optical discs entitled 2Electromagnetics for engineers3 Bearing the same call number and available at Koleksi Media PL2.
Includes bibliographical references (p. 389) and index
System requirements for accompanying CD-ROM: Windows: Pentium-class processor, at least 100 MHz, with 32 MBytes RAM. The CD has been tested with Windows 98, using Internet Explorer 5.5. Unix/Linux: The system should be no older than about 5 years and have at least 32 MBytes RAM. Netscape 4.7 has worked on all UNIX systems we have tried. Macintosh: PowerPC processor, at least 100 MHz, with 32 MBytes RAM. The CD has been tested on a variety of MAC platforms using Internet Explorer 5.0 and Java version MRJ 2.2.2. Adobe Acrobat reader
Keywords: Electromagnetism; Electromagnetism -- Industrial applications; Electromagnetic theory